"It's very saddening, you keep on wondering when the symptoms will be over": A qualitative study exploring the long-term chikungunya disease impact on daily life and well-being, 6 years after disease onset. - Churnalisa Doran; Ashley Duits; Adriana Tami; Izzy Gerstenbluth; Ajay Bailey (PLoS Neglected Tropical Diseases, 2023)
Background Long-term chikungunya is a mosquito-borne disease, characterized by disabling rheumatic symptoms persisting for years, after infection with the chikungunya virus. Previous studies focused on assessing the well-being of affected individuals from a quantitative perspective using generic instruments, and have reported physical and psychological impairment. However, a common critique is that generic instrument's structured responses and pre-defined health domains selected by health professionals, may not capture the full extent of well-being impairment experienced by patients. This study aimed to explore in-depth to which extent long-term chikungunya disease impacts daily living and the physical, psychological, and social well-being from the experiences and perspective of affected individuals. Methodology/principal findings Using open-ended questions, in-depth interviews were conducted with 20 purposively selected individuals with long-term chikungunya disease, in Curaçao. Interview audio-recordings were transcribed verbatim. The data were thematically analyzed. Living with persistent rheumatic symptoms affected the participant's daily living and well-being in several ways: experience of physical impact (restricted physical functioning and limitations in activities of daily life); experience of psychological impact (altered emotional state, fear of walking and running, psychosocial aspects of footwear adaptations, and uncertainty about disease progression and future health); and experience of social impact (social isolation and impaired relational maintenance, social dependency, challenges of social support, at-work productivity loss, and giving up leisure activities after work). Conclusions/significance This study, the first of its kind, indicated that the adverse impact of long-term chikungunya disease is currently underreported. The persistent rheumatic symptoms had a negative effect on functional ability, which in turn impacted broad aspects of daily life and well-being, beyond what is captured by generic instruments. In the view of the findings, physical exercise programs including manual therapy, aerobics, resistance and stretching exercises, and orthopaedic footwear interventions in a multidisciplinary patient-centred approach may improve physical function and subsequently overall well-being.